Abstracts of microbiological methods - Skerman, V. B. D.; International Committee on Nomenclature of Bacteria. Numerical Taxonomy Subcommittee (New York : Wiley-Interscience, 1969)
A selection of documents prepared for the 1964 Quebec conference of the Numerical Taxonomy Subcommittee of the International Committee on Nomenclature of Bacteria.
Includes bibliographical references.
Keywords: Microbiology -- Technique -- Abstracts